(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2019)
Research on the Consumption Preference for Rice Beetles (Sitophilus oryzae L) in Several Rice Varieties was carried out from March to Mei 2019 at Laboratory Science Center of PGRI University. The study aims to determine the consumption preferences of several rice varieties caused by rice beetles. The study used the Experimental method in a completely randomized design (CRD) with five treatments and five replications, namely white, red, black, white sticky rice and black sticky rice varieties. Based on the analysis of fingerprints, the treatment of white sticky rice varieties significantly affected the amount of lose weight rice and rice beetle consumption preference, then continued with the BNT Test. The treatment of varieties D (white sticky rice) was not significantly different from the treatment of varieties E (black sticky rice), treatment E (black sticky rice) significantly different from the treatment of variety C (black rice), the treatment of variety C (black rice) was not significantly different from the treatment of variety B (brown rice), treatment of variety B (brown rice) was significantly different from the treatment of variety A (white rice). Based on the BNT Test, rice beetle consumption preferences seen from the weight reduction of rice in D rice varieties had the greatest weight reduction of 6.6 grams and the lowest weight reduction was white rice varieties of 0.9 grams, while for red, black and Black sticky rice has an average weight loss of rice each of 4.1 grams, 4.2 grams and 5.7 grams. Based on the percentage of preference (preference) for rice beetle consumption, it was found that the highest percentage was found in white sticky rice varieties at 6.6% and the lowest in white rice varieties at 1.5%, while for brown rice varieties at 4%, black rice 4.2% and black sticky rice 5.6%.